FORMULASI DAN UJI AKTIVITAS ANTIOKSIDAN BODY LOTION EKSTRAK KOPI ROBUSTA (Coffea canephora) DENGAN METODE DPPH (2,2-difenil-1-pikrilhidrazil): English; Indonesia - Elisabeth Oriana Jawa La; I Komang Tri Musthika; Repining Tiyas Sawiji (Jurnal Ilmiah Manuntung: Sains Farmasi Dan Kesehatan, 2022)
The skin is the outermost part of the body and is very susceptible to exposure to free radicals. This can be prevented by using cosmetics that contain antioxidants. Coffee beans have the chemical compound chlorogenic acid which belongs to the phenolic group which is useful as an antioxidant. The purpose of this study was to formulate and test the antioxidant activity of Robusta coffee extract body lotion preparations.The method used is pure experiment and control class as a comparison. Analysis of physical quality data was carried out by means of descriptive analysis using tables based on the results of the average calculation of the physical quality test, antioxidant test using DPPH method, and statistical processing of hedonic test data using the One Way Anova test and continued with the Duncan test. The results showed that FII and FIII could be formulated into body lotion preparations and met the physical quality test requirements. The antioxidant test before storage obtained the IC50 value at FI of 47,61 ppm (AAI = 0,84); FII of 43,86 ppm (AAI = 0,91); and FIII of 34,07 ppm (AAI = 1,17) and after FI storage of 49,95 ppm (0,80); FII of 45,47 (AAI = 0,88); FIII of 36,11 ppm (AAI = 1,11). The results of the hedonic test showed that in the parameters of colour, aroma, texture, and comfort of use there were significant fifferences (<0,05), while the parameters of humidity and ease of rinsing alowed insignificant differences (>0,05). Based on the results obtained, Robusta coffee extract body lotion is able to ward off free radicals in the medium – strong category.